Letak Chalazion - Budihardjo, Budihardjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1980)
Chalazion cases attending the Eye Clinic of the Gadjah Mada University had been collected during 1978. It was found that the incidence of chalazion was 1,78%. Chalazion at the upper palpebra are more frequent than at the lower.Key Words: chalazion - blepharitis - palpebra - Meibomian glands - excochleation